Análise comparativa das propriedades química, microestrutural e mecânica das ligas 3004, recicladas das latas de alumínio, com e sem a adição de 3 % de níquel, solidificadas em molde de cobre - SILVA, Nelma Cristiane Siqueira da (2023)
Recycling materials is one of the factors that contribute to sustainable development on the planet. Aluminum recycling is a benchmark for the world industry, especially the packaging industry. In this work, two aluminum ingots recycled from post-consumer beverage cans, alloy AA3004, were obtained in order to compare their chemical, microstructural and mechanical properties, with the second ingot being modified by a 3% nickel content. The collected materials were sanitized, comminuted, pressed and subjected to melting. It was decided to use the copper mold for the solidification of ingots 1 (3004) and 2 (3004 + 3 % Ni). For the chemical characterization, the Optical Emission Spectrometry (EEO) technique was used, and the samples obtained from the two ingots were prepared through metallographic characterization. The microstructures were analyzed using Optical Microscopy (OM) and Scanning Electron Microscopy with Energy Dispersive System (SEM/EDS). In the mechanical characterization, the Vickers microhardness and tensile tests were performed. As a result of the study, it was observed that for the chemical characterization of ingot 1, only the element Mn presented a lower value (0,83 %), but not discrepant from that presented by the ABNT NBR ISO 209:2010 standard. For ingot 2, it was found that the element Mn also presented a lower percentage (0,84 %) and the value found for element Fe was higher according to the ABNT NBR ISO 209:2010 standard. The microstructures obtained are typical for Al-Mn and Al-Mn-Ni alloys. The microhardness obtained for ingot 1 was 55.76 HV and for ingot 2 its was 56.32HV. The tensile strength limit (LRT) showed that the mean value for ingot 1 was 109 MPa and for ingot 2 the mean value of the tensile strength limit was 140 MPa. Finally, the values obtained show that the ingot 2 presented a better result due to the presence of the element Ni.